An Analysis of Politeness Strategies of the Main Characters in “Enola Holmes 2” Movie - Nivi Annisa Amaliah Chaerdiani; Dewi Ekawati, Anita (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
In interacting between individuals, politeness strategies are needed. Where using polite language to maintain the emotional balance of the listener, so that the conversation remains harmonious. The purpose of this study is to introduce more about the types of politeness and explore the various politeness strategies that often appear in the film “Enola Holmes 2”. In analyzing the data, the researcher used Brown and Levinson’s (1987) theory of politeness strategies. This study uses a qualitative descriptive approach, focusing on the data of the main characters’ utterances in the film involving politeness strategies. The utterances were analyzed to identify various types of politeness strategies used by the main characters. The data collection method used was film observation. The results showed that 221 politeness strategy data were found in the film "Enola Holmes 2" including Bald-On Record 80 data (36%), Positive Politeness 90 data (41%), Negative Politeness 9 data (4%), and Off-Record 42 data (19%). The type of politeness strategy that appears most often in the film “Enola Holmes 2” is Positive Politeness. The researcher hopes that this study can be a source of reference for further research by exploring various focuses of research objects and conducting analyses with different approaches and applying different politeness theories, either in the context of films or in everyday life.